Tissue, cell type and stage-specific ectopic gene expression and RNAi induction in the Drosophila testis. - White-Cooper, H. (Spermatogenesis, 2012)
The Drosophila testis has numerous advantages for the study of basic cellular processes, as production of sperm requires a highly orchestrated and complex combination of morphological changes and developmentally regulated transitions. Experimental genetics using Drosophila melanogaster has advanced dramatically with the advent of systems for ectopic expression of genetic elements in specific cells. However the genetic tools used in Drosophila research have rarely been generated with the testes in mind, and the utility of relatively few systems has been documented for this tissue. Here I will summarize ectopic expression systems that are known to work for the testis, and provide advice for selection of the most appropriate expression system in specific experimental situations.